PROSES PENGAMBILAN KEPUTUSAN INTERNAL DI KANTOR INSPEKTORAT KABUPATEN MAMUJU - Supriadi Supriadi; Abd. Khalik (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2018)
The research used is descriptive. Data collection is done using technical field research (field research), library research and tracking data on line.Data collected from various sources to obtain sufficient data. Data obtained then analyzed qualitatively by explaining or describing the data being studied or obtained from the field , both primary data obtained from interviews, as well as from secondary data. The results of this study indicate that the internal decision-making process in the municipal inspectorate office has not been running optimally due to lack of proactive community to come directly inspectorate prepare what things are the requirements to take care of decision-making.